2020
DOI: 10.3892/ijmm.2020.4473
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional ephrinB2‑EphB4 signaling regulates the osteogenic differentiation of canine periodontal ligament stem cells

Abstract: The aim of the present study was to evaluate the effect of ephrinB2 gene-transfected canine periodontal ligament stem cells (cPdLScs) on the regulation of osteogenic differentiation. cPdLScs were transfected with a transgenic null-control green fluorescent protein (GFP) vector (termed Vector-cPDLSCs) or with NFNB2 GFP-Blasticidin (termed EfnB2-cPdLScs). Subsequently, the osteogenic differentiation of Vector-cPdLScs and EfnB2-cPdLScs was assessed by reverse transcription-quantitative polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Meanwhile, it is interesting to note that apart from cellular cementum, the PDL areas were also stained positively with ephrinB2 and EPHB4 during the root regeneration process. Previously, it was reported that the ephrinB2/EPHB4 signaling was able to regulate the osteogenic differentiation of PDL stem cells and cocultured preosteoblasts (S. Zhu et al, 2020;S. Y. Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it is interesting to note that apart from cellular cementum, the PDL areas were also stained positively with ephrinB2 and EPHB4 during the root regeneration process. Previously, it was reported that the ephrinB2/EPHB4 signaling was able to regulate the osteogenic differentiation of PDL stem cells and cocultured preosteoblasts (S. Zhu et al, 2020;S. Y. Zhu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is interesting to note that apart from cellular cementum, the PDL areas were also stained positively with ephrinB2 and EPHB4 during the root regeneration process. Previously, it was reported that the ephrinB2/EPHB4 signaling was able to regulate the osteogenic differentiation of PDL stem cells and cocultured preosteoblasts (S. Zhu et al, 2020; S. Y. Zhu et al, 2017). Similarly, it could be speculated that there might be ephrinB2/EPHB4 signaling transduction between PDL cells and cementoblasts in our study as well, since intercellular communication was easy within the dense periodontium.…”
Section: Discussionmentioning
confidence: 99%
“…Induced by LPS, TLR4 activates the pro-inflammatory transcription factor NF-κB that enters the nucleus and initiates pro-inflammatory gene transcription that encode the pro-inflammatory cytokines, IL-1 β , IL-6 and IL-8, leading to periodontal tissue destruction [ 54 ]. It increases the expression of Ephrin type-B receptor 4 (EphB4) and inhibits the expression of the protein EphrinB2 [ 74 ]. It also inhibits alkaline phosphatase activity, collagen type 1 Alpha 1, and the osteocalcin production and mineralization in the periodontal ligament stem cells proliferation.…”
Section: Immunoinflammatory Response In Oral Tissues Due To the Presence Of Endotoxins Released By P Gingivalis Generamentioning
confidence: 99%
“…Recent assays have reported the activation of EphrinB2/EphB4 increased osteogenic/odontogenic differentiation of hDPSCs and canine periodontal ligament stem cells (cPDLSCs) (Heng et al, 2018;Zhu et al, 2020). Moreover, EPO has been shown to regulate bone formation by activating EphrinB2/EphB4 signaling (Li, Shi, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Eph receptors belong to the receptor tyrosine kinase superfamily, and the interaction between ephrin ligands and their receptors contributes to bi‐directional signaling (Lisabeth et al, 2013). Recent assays have reported the activation of EphrinB2/EphB4 increased osteogenic/odontogenic differentiation of hDPSCs and canine periodontal ligament stem cells (cPDLSCs) (Heng et al, 2018; Zhu et al, 2020). Moreover, EPO has been shown to regulate bone formation by activating EphrinB2/EphB4 signaling (Li, Shi, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%